Zebrafish Experimental Animal Models for AD: A Comprehensive Review - Sande, Ruksar; Godad, Angel; Doshi, Gaurav (Current Reviews in Clinical and Experimental Pharmacology, 2024)
AD disease (AD) is a multifaceted and intricate neurodegenerative disorder characterized by intracellular neurofibrillary tangle (NFT) formation and the excessive production and deposition of Aβ senile plaques. While transgenic AD models have been found instrumental in unravelling AD pathogenesis, they involve cost and time constraints during the preclinical phase. Zebrafish, owing to their simplicity, well-defined behavioural patterns, and relevance to neurodegenerative research, have emerged as a promising complementary model. Zebrafish possess glutaminergic and cholinergic pathways implicated in learning and memory, actively contributing to our understanding of neural transmission processes. This review sheds light on the molecular mechanisms by which various neurotoxic agents, including okadaic acid (OKA), cigarette smoke extract, metals, and transgenic zebrafish models with genetic similarities to AD patients, induce cognitive impairments and neuronal degeneration in mammalian systems. These insights may facilitate the identification of effective neurotoxic agents for replicating AD pathogenesis in the zebrafish brain. In this comprehensive review, the pivotal role of zebrafish models in advancing our comprehension of AD is emphasized. These models hold immense potential for shaping future research directions and clinical interventions, ultimately contributing to the development of novel AD therapies.
Keywords: transgenic models